Improving Students’ Writing Skills through Computer-Based Concept Mapping - Irwandi Irwandi; Yulia Isnaini; Muhammad Hudri (Muhammadiyah University of Mataram, 2021)
The purpose of this study was to find out how the computer-based concept mapping as a teaching strategy could solve the students’ problems in learning English writing. The students had low score in writing test and did not actively participate in the teaching and learning process. The research design was a collaborative classroom action research, and there were 30 university students participated. To obtain the data, a writing test and some questionnaires were administered. The test was to evaluate students’ writing ability and the questionnaire was to collect students’ responses of the teaching and learning process. The findings showed that there were much improvement of their writing skill and learning attitude. The number of students who passed the criteria of success was 27 out of 30 students, and they mostly agreed that concept mapping is a helpful and interesting writing tool